Greigite as an Indicator for Salinity and Sedimentation Rate Change: Evidence From the Yangtze River Delta, China. Issue 3 (1st March 2021) - Chen, Yinglu; Zhang, Weiguo; Nian, Xiaomei; Sun, Qianli; Ge, Can; Hutchinson, Simon M.; Cheng, Qinzi; Wang, Feng; Chen, Jin; Zhao, Xuanqi
Abstract: Ferrimagnetic greigite (Fe3 S4 ) is widespread in the sedimentary environment. Despite abundant reports of greigite occurrence in marine and lacustrine deposits, its formation mechanisms in deltaic deposits remain poorly studied. Here we investigate greigite in Holocene Yangtze River Delta deposits using granulometric, magnetic, and geochemical methods. The studied cores consist of tidal river, estuary, shallow marine, and delta facies in ascending order. The greigite‐bearing layers are found predominantly in the accreting tidal flat facies during the transgression stage and secondarily in the shallow marine facies during the regression stage of the delta's Holocene development. These sedimentary intervals have a higher total sulfur (TS) content and TS to total organic carbon ratios (TS/TOC) suggesting the accumulation of iron sulfides, including greigite, under reducing estuarine and shallow marine conditions. The greigite‐bearing layers in the tidal flat facies have lower Sr/Ba ratios, in comparison to the shallow marine facies, indicating a lower salinity environment. Supported by the dating results, it is suggested that the higher sedimentation rate of the tidal flat facies, caused by rapid sea‐level rise during the early Holocene, favors the formation and preservation of greigite. Our results indicate that the magnetic detection of greigite provides a simple and useful tool for inferring salinity and sedimentation rate changes, and hence better an understanding of the heterogeneity of depositional processes in Holocene delta environments. Plain Language Summary: Greigite (Fe3 S4 ), an early or late diagenetic magnetic mineral, is an iron sulfide commonly produced during the carbon‐iron‐sulfur (C‐Fe‐S) cycle in aquatic environments. Its occurrence is generally found to be linked to water salinity change, which can be used to infer changes in past environmental conditions such as drought and flood events. So far, studies on greigite have focused on marine and lacustrine deposits. Its formation mechanisms in delta environments remain poorly known, where fresh and marine water mixing results in intensive spatial and temporal salinity change. In this study, environmental magnetic measurement and salinity indictors for example, the ratio of strontium to barium (Sr/Ba), the ratio of total sulfur to total organic carbon (TS/TOC) and TS concentration are combined to reveal greigite occurrence and its formation conditions. Our results show that higher sedimentation rates and marked salinity change associated with rapid sea level rise in the early Holocene is favorable for greigite generation and preservation. We find that magnetic detection of greigite can provide valuable information regarding spatial/temporal variabilities in fresh‐marine water mixing and depositional processes in deltaic environment. Key Points: We identify greigite at the boundary of sedimentary facies with marked salinity change in the Yangtze River Delta Greigite‐bearing layers occurs predominantly in accreting tidal flat facies with a higher sedimentation rate Magnetic identification of gregite can assist stratigraphic differentiation in delta deposits